China's forests: global lessons from market reforms (Chinese) - Hyde, William F.; Belcher, B.; Jintao Xu (Resources for the Future and Center for International Forestry Research, 2005)
This book examines the experience of China's forestry sector with respect to the full set of forest and nonforest policy reforrms introduced since 1978. The lessons of this book are important for China, and for the rest of the world as well. For China the analyses in each chapter provides rigorous evidence on those policies that have worked and on how well the have worked. The book consists of 10 chapters: 1. Hyde, W.F., Jintao Xu, Belcher, B. Introduction and Appendix table: policy reform in China's forestry; 2. Liu Dachang, Edmund, D. Devolution as a means of expanding local forest management in South China: lessons from the past 20 years; 3. Jinlong Liu, Landell-Mills, N. Taxes and fees in the Southern collective forest region; 4. Runsheng Yin. Central characteristics of reform: measures of the effects of improved property rights, a stable policy environment, and environmental protection; 5. Daowei Zhang. Policy reform and investment in forestry; 6. Rozelle, S., Jikun Huang, Benziger, V. Forest exploitation and protection in reform China: assessing the impacts of policy and economic growth; 7. Yaoqi Zhang, Uusivuori, J., Kuuluvainen, J., Kant, S. Deforestation and reforestation in Hainan: roles of markets and institution; 8. Ruiz-Perez, M., Belcher, B., Maoyi Fu, Xiaosheng Yang. Forestry, poverty, and rural development: perspectives from the bamboo sector; 9. Sayer, J.A., Changjin Sun. Impacts of policy reforms on forest environments and biodiversity; 10. Hyde, W.F., Jintao Xu, Belcher, B., Runsheng Yin, Jinlong Liu. Conclusions and policy implications.